(3HOjYI GdGMSGf aj Ndb GdGfSGfs ((3jMi GdOjSWi Hf aNQ GdOjf Hf Ydi Hf TeS GdOjf eMeO GdeGdci s)
(3ChdgG (B:s
(3gPG cJGH HOjYI GdGMSGf ai Ndb GdGfSGf , hSejJg HgPG GdJQLeI , hQJHJg Ydi GdMQha GdeYLeI jbGd gPG RhL GdeQCI hHYdgG , hNdjdgG hbQjfgG s
(3BNQgG (B:s
(3ef MQa GdjGA , bhdg (B:(3QLd jdeYi hCdeYi hGdjbf GdeSf GdcHjQ hGdjSQ hGdjGSQI GdPi jONd ai GdejSQ , hgh GdbeGQ GdjYShH GdSjO hGddg SHMGfg hJYGdi CYde Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3eQJH Ydi MQha GdeYLes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs